Empowering marginal communities with information networking - Rahman, Hakikur, 1957- (Hershey, PA : Idea Group Pub., 2006)
'This book details how new technologies can help people living in poverty improve their livelihood, increase productivity, improve the quality of services, and empower them if technologies are used in ways that are appropriate to their context and needs'--Provided by publisher
Includes bibliographical references and index
Keywords: Information technology -- Developing countries; Technological innovations -- Developing countries; Community development -- Developing countries; Marginality, Social; Social networks